1983
DOI: 10.1007/bf01907439
|View full text |Cite
|
Sign up to set email alerts
|

Decreased incidence of ventricular fibrillation after an acute coronary artery ligation in exercised pigs

Abstract: Evidence has been presented that regular physical activity may be associated with a decreased incidence of sudden cardiac death. It has been suggested that self-selection of those engaging in regular exercise rather than the physical activity itself is a major factor in explaining these results. We therefore studied the effects of a two-month exercise program on the incidence of ventricular fibrillation after an acute ligation of the left anterior descending (LAD) coronary artery in domestic Yorkshire pigs. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…We also noticed that falipamil and alinidine both decreased LVdP/dtmax dose dependently when heart rate was fixed by atrial pacing and that the magnitude of these changes were very similar during pacing and normal sinus rhythm [17,19]. This last observation is most likely explained by the observation that, at least in anesthetized pigs, LVdP/dtmax is not very sensitive to changes in heart rate in the range of 100-150 beats/min [20]. In three preliminary experiments in anesthetized pigs, we have observed that UL-FS 49 did not significantly decrease LVdP/ dtmax, when heart rate was kept constant by atrial pacing at 110 bpm.…”
Section: Discussionmentioning
confidence: 69%
“…We also noticed that falipamil and alinidine both decreased LVdP/dtmax dose dependently when heart rate was fixed by atrial pacing and that the magnitude of these changes were very similar during pacing and normal sinus rhythm [17,19]. This last observation is most likely explained by the observation that, at least in anesthetized pigs, LVdP/dtmax is not very sensitive to changes in heart rate in the range of 100-150 beats/min [20]. In three preliminary experiments in anesthetized pigs, we have observed that UL-FS 49 did not significantly decrease LVdP/ dtmax, when heart rate was kept constant by atrial pacing at 110 bpm.…”
Section: Discussionmentioning
confidence: 69%
“…The question therefore remains to what extent the increase in LVdP/dtmo, induced by these pyridazinone derivatives reflects true positive inotropy. In anaesthetized pigs we have shown that increasing heart rate, by atrial pacing, from 100 beats min-' to 160 beats min-' has no effect on LVdPldtmax (Scheffer & Verdouw, 1983). Although we have no such data in the conscious animal, it appears unlikely that LVdP/dt,, would more than double when heart rate increases only by 30%.…”
Section: Discussionmentioning
confidence: 85%
“…Concerning the first point, selection of pigs for physiological characteristics such as cardiovascular capacity rather than for production only is one option. With regard to the second point, it is known that also in pigs cardiovascular development is positively influenced by physical exercise (28). In the current system, pigs do not get much exercise, most of their time is devoted to either sleeping or eating.…”
Section: Pathophysiology and Disease Prevention In Pigsmentioning
confidence: 99%